STATE OF RESOURCES AND FISHERY OF MANILA CLAM RUDITAPES PHILIPPINARUM (ADAMS ET REEVE, 1848) IN THE LOSOS BIGHT AND BUSSE LAGOON (ANIVA BAY, OKHOTSK SEA) IN 2010–2016 - A. Ch. Kim (Известия ТИНРО, 2019)
Landings of manila clam Ruditapes philippinarum were steady high in 2010–2016 and exceeded the recommended volume that caused deterioration of its resources in the areas of large aggregations. Any significant growth of the clam colonies in the surveyed area could not be expected in the nearest future because of continuing press of fishery. Total stock of Ruditapes philippinarum in the Aniva Bay is estimated as 240 t, including 203 t of clams with commercial size.